Epidemiology, antimicrobial resistance and outcomes of Staphylococcus aureus bacteraemia in a tertiary hospital in Fiji: A prospective cohort study - Michael J. Loftus; Tracey E.M.W. Young-Sharma; Shitanjni Wati; Gnei Z. Badoordeen; Luke V. Blakeway; Sally M.H. Byers; Allen C. Cheng; Adam W.J. Jenney; Ravi Naidu; Amitesh Prasad; Vinita Prasad; Litia Tudravu; et al. (Elsevier, 2022)
Summary: Background: Staphylococcus aureus bacteraemia (SAB) is one of the commonest bloodstream infections globally and is associated with a high mortality rate. Most published data comes from temperate, high-income countries. We describe the clinical epidemiology, microbiology, management and outcomes of patients with SAB treated in a tropical, middle-income setting at Fiji's largest hospital. Methods: A prospective, observational study was performed of consecutive SAB cases admitted to Colonial War Memorial Hospital (CWMH) in Suva, between July 2020 and February 2021. Detailed demographic, clinical and microbiological data were collected, including the key outcome of in-patient mortality. To estimate the population incidence, all SAB cases diagnosed at the CWMH laboratory were included - even if not admitted to CWMH - with the population of Fiji's Central Division used as the denominator. Findings: A total of 176 cases of SAB were detected over eight-months, which equated to an incidence of 68.8 cases per 100,000 population per year. Of these, 95 cases were admitted to CWMH within 48 h of index culture. Approximately 8.4% (8/95) of admitted cases were caused by methicillin-resistant Staphylococcus aureus (MRSA). All cause in-patient mortality was 25.3%, increasing to 55% among patients aged 60 or older. Interpretation: This reported incidence of SAB in central Fiji is one of the highest in the world. SAB was associated with significant mortality, especially in those over 60 years of age, despite a relatively low frequency of methicillin resistance. Funding: Supported by the National Health and Medical Research Council (Australia) and the GRAM (Global Research on Antimicrobial Resistance) Project, Oxford University (United Kingdom).